IL-17A Neutralization Improves the Neurological Outcome of Mice With Ischemic Stroke and Inhibits Caspase-12-Dependent Apoptosis - Dai, Qingqing; Han, Song; Liu, Ting; Zheng, Jiayin; Liu, Cui; Li, Junfa; Li, Shujuan (Frontiers in Aging Neuroscience, 2020)
We previously reported that the levels of astrocyte-derived interleukin-17A (IL-17A) increased both in the peri-infarct region and cerebrospinal fluid (CSF) of mice with 1-h middle cerebral artery (MCA) occlusion/12-h reperfusion (1-h MCAO/R 12 h)-induced ischemic stroke. However, the effects of IL-17A neutralization on the neurological outcome of mice with ischemic stroke and its underlying molecular mechanism are unclear. In this study, we found that the intracerebroventricular injection of IL-17A-neutralizing monoclonal antibody (mAb; 2.0 μg) could reduce the infarct volume, alleviate neuron loss, and improve the neurological outcomes of mice with 1-h MCAO/R 24-h- or 3-day-induced ischemic-stroke mice. The IL-17A neutralization could also significantly inhibit the increase of pro-caspase-3 cleavage through caspase-12-dependent cell apoptosis, as well as preventing the decrease of antiapoptotic factor B-cell lymphoma 2 (Bcl-2) and the increase of proapoptotic Bcl-2-associated X protein (Bax) in the peri-infarct region of mice following ischemic stroke. In addition, we confirmed that the recombinant mouse (rm) IL-17A could significantly aggravate 1-h oxygen–glucose deprivation/24-h reoxygenation (1-h OGD/R 24 h)-induced ischemic injuries in cortical neurons in a dose-dependent manner, and the rmIL-17A could also exacerbate neuronal apoptosis through caspase-12 (not caspase-8 or caspase-9)-dependent pathway. These results suggest that IL-17A neutralization could improve the neurological outcome of mice with ischemic stroke through inhibiting caspase-12-dependent neuronal apoptosis.